2015
DOI: 10.1111/njb.00889
|View full text |Cite
|
Sign up to set email alerts
|

Aristolochia phuphathanaphongiana sp. nov. from southwestern Thailand

Abstract: Aristolochia phuphathanaphongiana Do sp. nov. from southwestern Thailand is described here. The new species is most similar to A. acuminata and A. kongkandae, but it is distinguished by having a broad‐ovate to cordate bracteole that is sessile and 8–15 × 6–12 mm, the entire perianth being dark purple to maroon black, with lanceolate limb and abaxial surface densely covered with long grey hairs, as well as by non‐winged seeds. In addition to the description, a key to the species of Aristolochia subsect. Podanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…It can be distinguished from Aristolochia by the follow-ing set of characters: perianth strongly curved, gynostemium 3-lobed, anthers paired on the outer surface of each gynostemium segment, and capsule dehiscing basipetally (Do et al 2015a;Zhu et al 2019a). Several new species of Isotrema have been found and described from China and its neighbouring countries during recent years (Liu and Deng 2009;Xu et al 2011;Yao 2012;Huang et al 2013Huang et al , 2015Wu et al 2013Wu et al , 2015Do et al 2014Do et al , 2015aDo et al , 2015bDo et al , 2015cDo et al , 2015dDo et al , 2016Do et al , 2019Huong et al 2014;Lu and Wang 2014;Ohi-Toma et al 2014;Zhu et al 2015Zhu et al , 2016Zhu et al , 2017aZhu et al , 2017bZhu et al , 2018Zhu et al , 2019bZhu et al , 2019cGong et al 2018;Yang et al 2018;Li et al 2019;Peng et al 2019;Zhou et al 2019;Cai et al 2020aCai et al , 2020b. Currently, a total of 106 species have been reported from Isotrema, most of which are distributed in eastern and southern Asia, with some species further extended to northern and central America (Zhu et al 2019a).…”
mentioning
confidence: 99%
“…It can be distinguished from Aristolochia by the follow-ing set of characters: perianth strongly curved, gynostemium 3-lobed, anthers paired on the outer surface of each gynostemium segment, and capsule dehiscing basipetally (Do et al 2015a;Zhu et al 2019a). Several new species of Isotrema have been found and described from China and its neighbouring countries during recent years (Liu and Deng 2009;Xu et al 2011;Yao 2012;Huang et al 2013Huang et al , 2015Wu et al 2013Wu et al , 2015Do et al 2014Do et al , 2015aDo et al , 2015bDo et al , 2015cDo et al , 2015dDo et al , 2016Do et al , 2019Huong et al 2014;Lu and Wang 2014;Ohi-Toma et al 2014;Zhu et al 2015Zhu et al , 2016Zhu et al , 2017aZhu et al , 2017bZhu et al , 2018Zhu et al , 2019bZhu et al , 2019cGong et al 2018;Yang et al 2018;Li et al 2019;Peng et al 2019;Zhou et al 2019;Cai et al 2020aCai et al , 2020b. Currently, a total of 106 species have been reported from Isotrema, most of which are distributed in eastern and southern Asia, with some species further extended to northern and central America (Zhu et al 2019a).…”
mentioning
confidence: 99%
“…Both two new species with horseshoe-shaped perianth, the 3-lobed gynostemium and each lobe consisting of one pair oblong stamens belongs to Aristolochia subgenus Siphisia (Ma 1989a). These new discoveries, along with many new species recently described from China and neighbouring countries (Phuphathanaphong 2006; Liu and Deng 2009; Xu et al 2011; Yao 2012; Huang et al 2013, 2015; Wu et al 2013; Do et al 2014, 2015a, 2015b, 2015c, 2015d, 2017; Huong et al 2014; Lu and Wang 2014; Ohi-Toma et al 2014; Ravikumar et al 2014; Zhu et al 2015, 2016, 2017a, 2017b, 2018; Gong et al 2018; Yang et al 2018) provide evidence that the genus Aristolochia and especially Aristolochia subgenus Siphisia is very diverse in South-East Asia. We predict that more new species of Aristolochia will be found after extensive investigations in this region.…”
Section: Discussionmentioning
confidence: 74%
“…Isotrema sanyaense can also be easily distinguished from I. jianfenglingense by the inflorescence (cymes 1–5-flowered, in hanging clusters of 1 to numerous branches vs. solitary), the calyx (white with purple-red stripes vs. light red to brown without stripes), the calyx limb (discoid, yellow, with purple-red stripes and spots, lobes without papillae and pubescent vs. trumpet-shaped, pink, without stripes and spots, lobes densely papillae and pubescent), and the throat (dark red without spots, significantly smaller than the limb width vs. pink with red-brown spots, approximately to the limb width) (summarized in Table 1). Considering the discovery of this new species from Hainan island, along with the species previously described in China, Myanmar, Peninsular Malaysia, Thailand and Vietnam in recent years (González and Poncy 1999, Phuphathanaphong 2006, Hansen and Phuphathanaphong 2009, Liu and Deng 2009, Xu et al 2011, Yao 2012, Huang et al 2013, 2015, Wu et al 2013, 2015, Do et al 2014, 2015a, 2015b, 2015c, 2015d, 2017, 2019, Huong et al 2014, Lu and Wang 2014, Ohi-Toma et al 2014, Ravikumar et al 2014, Zhu et al 2015, 2016, 2017a, 2017b, 2018, Gong et al 2018, Yang et al 2018, Zhou et al 2019), we predict that more and more new species of Isotrema will be found after extensive investigations and studies.…”
Section: Discussionmentioning
confidence: 96%